IMPLEMENTASI MEANINGFUL LEARNING SEBAGAI BAGIAN DARI DEEP LEARNING UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA DI KELAS 5 - Yarnas, Syrly; Wilna Simangunsong, Tamara; Buana Tungga Dewi, Tri; Muthi’ah Utami, Tri; Muhdantiar, Wildan; Prima Mutia Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesian language holds an important position in the national education system as a primary instrument for shaping students' identity, communication, and literacy skills. However, the learning outcomes of fifth-grade students in understanding main idea material remain low, caused by one-way learning practices that rarely connect the material to students' real-life experiences. This project intends to improve the Indonesian language learning results of fifth-grade students by implementing Meaningful Learning as part of Deep Learning. This study used the Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, with three cycles of preparation, action, observation, and reflection. The subjects of this study were 30 fifth-grade students of SDN Ciracas 5 in the 2025/2026 academic year, learning accomplishment exams are administered at the conclusion of each cycle, and observation sheets serve as research tools. The findings revealed a progressive improvement in learning completeness, from 43% (13 students) in the pre-cycle to 53% (16 students) in Cycle I, 70% (21 students) in Cycle II, and 80% (24 students) in Cycle III, surpassing the minimal completion requirement of 75%. This improvement was supported by progressive refinements, including the use of more varied learning media, connecting material to students' real-life contexts, and the application of collaborative discussions with interactive digital media. Thus, the implementation of Meaningful Learning as part of Deep Learning proved effective in enhancing fifth-grade pupils' Indonesian language learning results on main idea material.